Pilar's Existence in Her Love Story Shown in Paulo Coelho's By The River Piedra I Sat Down And Wept (NOBEL: Journal of Literature and Language Teaching, 2016)
This research talks about existence found in By the River Piedra I Sat Down and Wept novel by Paulo Coelho. This research focuses on Pilar as one of the main characters in the novel. The aim of this research is to describe Pilar's characteristics and Pilar's life to get her existence through her love story in the novel. It is a descriptive study. It is a library-based study that collects data from the novel. The result of this research shows that Pilar as one of the main characters in the novel is a dynamic character. Pilar is initially described as lacking self-confidence and a fearful woman and she finally becomes a self-confident and brave woman. Besides that, the love story of Pilar's life brings Pilar to some stages of existence that is aesthetic stage, ethic stage and religious stage as the peak of stage in life.